Sickness Presenteeism Among the Swedish Self-Employed During the Covid-19 Pandemic - Vinberg, Stig; Landstad, Bodil J.; Tjulin, Åsa; Nordenmark, Mikael (Frontiers in Psychology, 2021)
The present study analyzed the impact of business operations, work and family circumstances, and well-being on the risk of sickness presenteeism for Swedish self-employed workers during the Covid-19 pandemic. It is of great importance to investigate the impact of the pandemic on the self-employed and their enterprises because they are seen as key drivers of economic growth and constitute an expanding group in many countries. Data were obtained from 845 self-employed workers by a web-based survey including questions about background information, work and family circumstances, well-being, sickness presenteeism, and questions about the pandemic. Results were that around 40% of the self-employed introduced new products, processes, and marketing methods, and just over 50% attempted to get new customers during the pandemic. Nearly half of the self-employed people reported that they lost contracts, and 22% judged the risk of bankruptcy to be quite or highly likely. Regression analyses showed that the more the self-employed reported impact on business operations, increased work hours, a higher level of work-family conflict, and a lower level of self-rated health, the higher the risk of sickness presenteeism. The most common reasons given by the participants for sickness presenteeism during the pandemic were ‘nobody else can carry out my responsibilities’, ‘I can’t afford to take sick leave’ and ‘I enjoy my work’. Conclusions are that a critical event such as the pandemic probably adds to an already high workload for the self-employed. Impact on business operations such as developing new products/services and marketing, risk of bankruptcy and increased work hours seems to be important factors for explaining sickness presenteeism among the self-employed. Theoretical contributions from the study suggest that critical events such as the Covid-19 pandemic should be considered as an important environmental factor when studying sickness presenteeism among self-employed.